Critical Assessment on Unmet Oral Health Needs and Oral Health-related Quality of Life Among Old Age Home Inhabitants in Karnataka, India - M R; Sen M; Mala K; Sujir N; Poojary D; Shetty NJ; Shenoy R; Saldanha S (Dove Medical Press, 2021)
Roma M,1,2 Madhura Sen,1,2 Kundabala Mala,1,2 Nanditha Sujir,2,3 Dharnappa Poojary,2,4 Neetha J Shetty,2,5 Ramya Shenoy,2,6 Sharon Saldanha2,7 1Department of Conservative Dentistry and Endodontics, Manipal College of Dental Sciences, Mangalore, Mangalore, India; 2Manipal Academy of Higher Education, Manipal, Karnataka, India; 3Department of Oral Medicine and Radiology, Manipal College of Dental Sciences, Mangalore, Mangalore, India; 4Department of Oral & Maxillofacial Surgery, Manipal College of Dental Sciences, Mangalore, Mangalore, India; 5Department of Periodontology, Manipal College of Dental Sciences, Mangalore, Mangalore, India; 6Department of Public Health Dentistry, Manipal College of Dental Sciences, Mangalore, Mangalore, India; 7Department of Prosthodontics and Crown and Bridge, Manipal College of Dental Sciences, Mangalore, Mangalore, IndiaCorrespondence: Ramya ShenoyDepartment of Public Health Dentistry, Manipal College of Dental Sciences, Mangalore, Light House Hill Road, Mangalore, Karnataka, 575001, IndiaTel +91 9880450277Email ramya.shenoy@manipal.eduSharon SaldanhaDepartment of Prosthodontics and Crown and Bridge, Manipal College of Dental Sciences, Mangalore, Light House Hill Road, Mangalore, Karnataka, 575001, IndiaEmail sharon.saldanha@manipal.eduPurpose: To critically assess the unmet oral health needs and oral health-related quality of life among old age home inhabitants in Karnataka, India.Methods: A total of 96 older adults (males=32, 33.33%, females=64, 66.67%) aged 60 years and above, residing in old age homes were included in this cross-sectional study. The mean age of the participants included in the study was 69.25± 7.99 years. Oral health status and dental needs were assessed using the Oral Hygiene Index Simplified (OHIS) and the WHO Oral Health Assessment forms. Oral health-related quality of life was evaluated by administrating the Geriatric Oral Health Assessment Index (GOHAI) questionnaire through an interview format.Statistical Analysis: The Statistical Package for Social Sciences (SPSS) version 17 was used. Descriptive statistics was tabulated for oral health status and GOHAI scores. Student’s t-test and ANOVA were applied to check the association of the GOHAI responses with the number of years of residence in old age homes, age groups, gender, and dentition status.Results: The mean age of the participants included in the study was 69.25± 7.99 years. Twenty-six (27.1%) participants reported diabetes mellitus and hypertension. Most of the participants 89 (91.7%) visited the dentist when they had dental complaints. Among the dentulous study population, the majority of the participants had untreated dental caries indicated for dental extraction and needed periodontal therapy. Amongst the participants, 68 (70.82%) required prosthetic rehabilitation. More than 10 years of residence in old aged homes, over 80 years of age, being female, and completely edentulous groups showed lower total GOHAI scores compared to their counterparts.Conclusion: The majority of the participants showed unmet oral health needs and lower GOHAI scores indicating poor oral health-related quality of life.Keywords: developing countries, homes for aged, GOHAI, older adults, oral health, oral health-related quality of life